1992
DOI: 10.2331/suisan.58.1211
|View full text |Cite
|
Sign up to set email alerts
|

Sex Control of the Japanese Eel by an Estrogen(DES-Na) in Feed.

Abstract: The sex of the Japanese eel could be controlled by the oral administration of DES-Na (sodium diethylstilbestrol) which also promoted growth. Elvers were reared from glass eels for more than 500 days with a commercial feed which contained DES-Na (0 , 0.5, 0.75, 1.0 ppm).All the eels were dissected at the end of the experiment to check the sex by both external appearance and histological examinations of gonads.The sex groups were divided into male, male?, female, female? and unknown by their external appearance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
5
25
0
Order By: Relevance
“…The proportion of AI eels was very low, representing 1.4% (2/140) of eels investigated at the microscopic level. This is comparable to what was found in A. japonica kept in similar conditions [Satoh et al, 1992]. These authors designed an experiment to assess the effect of an estrogen treatment on sex ratio and found 1.7% of hermaphrodite eels in the control group.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The proportion of AI eels was very low, representing 1.4% (2/140) of eels investigated at the microscopic level. This is comparable to what was found in A. japonica kept in similar conditions [Satoh et al, 1992]. These authors designed an experiment to assess the effect of an estrogen treatment on sex ratio and found 1.7% of hermaphrodite eels in the control group.…”
Section: Discussionsupporting
confidence: 55%
“…1978; Takahashi, 1979;Satoh et al, 1992;Lokman and Young, 1998]. The 2 AI European eels described in the present study were fortuitously identified during the course of a previous experiment aiming to compare aromatase gene expression between females, males and juvenile intersexual eels.…”
mentioning
confidence: 99%
“…For example, 17a-ethynylestradiol induced ovarian differentiation in 90% of 60-80 mm LT elvers, 65% of 150-180 mm yellow eels, and had only a moderate feminizing influence on 220-250 mm LT yellow eels (Colombo and Grandi, 1995). Oestrogens may also have a feminizing effect on older individuals with macroscopically differentiated gonads (Satoh et al, 1992). Increasing the dose (Degani and Kushnirov, 1992;Satoh et al, 1992;Tzchori et al, 2002) and the duration of exposure (Anderson et al, 1996;Tzchori et al, 2002) may also influence the final sex ratio in favor of females.…”
Section: Hormonal Interventionmentioning
confidence: 93%
“…Female sex steroids, such as diethylstilbestrol, 17ß-estradiol and 17a-ethynylestradiol, stimulate the development of ovaries and can increase markedly the proportion of females produced (Table 2). In most cases feminization is accompanied by increased growth (Degani, 1986a;Satoh et al, 1992;Chiba et al, 1993;Anderson et al, 1996;Grandi et al, 2000;Tzchori et al, 2002;Degani et al, 2003). Naturally occurring plant hormones, phytoestrogens, may also have a significant feminizing effect (Tzchori et al, 2002).…”
Section: Hormonal Interventionmentioning
confidence: 95%
See 1 more Smart Citation